2006
DOI: 10.1080/09540250600980568
|View full text |Cite
|
Sign up to set email alerts
|

School exclusions and masculine, working‐class identities

Abstract: In this paper attention will be paid to issues arising from school-based research into the experience of working-class boys who are excluded. National and local school exclusion statistics indicate an overall gender imbalance: in the secondary school sector, for every four boys who are excluded only one girl is excluded. Furthermore, statistics show that other groups such as pupils living in poverty (as indicated by receipt of free school meals) have an increased likelihood of being excluded from school. Expla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 11 publications
0
22
0
4
Order By: Relevance
“…The relevance of the absence literature to this present study is that this body of research unequivocally concludes missing school is harmful to both current and future educational outcomes (Dreyfoos, 1990;Finn, 1993;Lehr, Sinclair, & Christenson, 2004;Stouthamer-Loeber & Loeber, 1988). In addition to lower standardized testing achievement levels correlated with missing school (Gottfried,School Effectiveness and School Improvement 5 2009), students with higher track records of absence behavior face additional educational and economic consequences, including grade retention (Neild & Balfanz, 2006), high school dropout (Rumberger, 1995;Rumberger & Thomas, 2000), and future unemployment (Alexander, Entwisle, & Horsey, 1997;Broadhurst, Patron, & May-Chahal, 2005;Kane, 2006). Students who miss school more frequently also face higher risks of smoking tobacco, consuming alcohol, and using drugs (Halfors et al, 2002).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…The relevance of the absence literature to this present study is that this body of research unequivocally concludes missing school is harmful to both current and future educational outcomes (Dreyfoos, 1990;Finn, 1993;Lehr, Sinclair, & Christenson, 2004;Stouthamer-Loeber & Loeber, 1988). In addition to lower standardized testing achievement levels correlated with missing school (Gottfried,School Effectiveness and School Improvement 5 2009), students with higher track records of absence behavior face additional educational and economic consequences, including grade retention (Neild & Balfanz, 2006), high school dropout (Rumberger, 1995;Rumberger & Thomas, 2000), and future unemployment (Alexander, Entwisle, & Horsey, 1997;Broadhurst, Patron, & May-Chahal, 2005;Kane, 2006). Students who miss school more frequently also face higher risks of smoking tobacco, consuming alcohol, and using drugs (Halfors et al, 2002).…”
Section: Introductionmentioning
confidence: 58%
“…In identifying significant classroom contextual factors for urban elementary youth, the results of this study can be used to develop policy and support interventions early in schooling. The focus on early school years is crucial for policy makers, as prior research has suggested that for urban students, missing school (i.e., full day absences) in early years of schooling has been found to be related to both diminished current and future educational outcomes, including lower testing performance, increased probability of grade retention, higher high school dropout rates, fewer employment opportunities, and greater chance of engaging in illegal activities (Alexander et al, 1997;Balfanz & Byrnes, 2006;Broadhurst et al, 2005;Gottfried, 2009Gottfried, , 2010Kane, 2006;Neild & Balfanz, 2006). Hence, documenting the effects of missing school for elementary school students will enable the early remediation of young urban students at risk for educational failure, before they enter into secondary education where the ramifications of missing school become increasingly harmful to the probability of both schooling and economic success.…”
Section: Ma Gottfriedmentioning
confidence: 99%
“…Simply stated, absenteeism is harmful. Although much of the work in the area of absences is correlational (for more causal studies, see Gershenson, Jacknowitz, & Brannegan, 2016; Goodman, 2014; Gottfried, 2010, 2011b; Marcotte & Hemelt, 2008), research has unequivocally found that children who miss school tend to have lower standardized testing outcomes, higher chances of grade retention and dropout, more difficulty with social development and greater feelings of alienation, increased drug and alcohol use once in young adulthood, and worsened employment prospects (Alexander, Entwisle, & Horsey, 1997; Broadhurst, Paton, & May-Chahal, 2005; Chen & Stevenson, 1995; Connell, Spencer, & Aber, 1994; Ekstrom, Goertz, Pollack, & Rock, 1986; Finn, 1993; Gershenson et al, 2016; Goodman, 2014; Gottfried, 2009, 2010, 2011b, 2014; Hallfors et al, 2002; Kane, 2006; Morrissey, Hutchison, & Winsler, 2014; Newmann, 1981). More so, it has been established that a spillover effect exists in regard to absenteeism; when classmates miss more school, all students in the classroom tend to have lower test scores (Gottfried, 2011a, in press).…”
Section: The Status Of Student Absenteeismmentioning
confidence: 99%
“…Highly absent students also tend to engage in both current and future health-risk behaviors, such as smoking and alcohol and drug use (Hallfors et al, 2002;Wang, Blomberg, & Li, 2005). Economically, students who are more frequently absent also face greater future economic hardships, such as unemployment (Alexander et al, 1997;Broadhurst et al, 2005;Kane, 2006).…”
mentioning
confidence: 99%